THE INFLUENCE OF LACTATION MANAGEMENT HEALTH EDUCATION ON THE LEVEL OF KNOWLEDGE AND SELF-EFFICACY OF BREASTFEEDING MOTHERS AT MAEMUNAH MIDWIFE CLINIC - Mahfuzi, Mahfuzi; Novita, Novita (HEARTY, 2024)
Background: In 2020, UNICEF reported that the global coverage of exclusive breastfeeding was 38%, with developing countries at only 39%. Exclusive breastfeeding coverage in ASEAN countries such as India reached 46%, the Philippines at 34%, Vietnam at 27%, and Myanmar at 24%. In Indonesia, the exclusive breastfeeding coverage in 2022 was only 67.96%. Three reasons contribute to breastfeeding cessation: incorrect latch causing newborns difficulty in sucking (27.1%), breast milk not meeting infant needs (55.6%), and mothers believing they do not produce enough milk (52.2%). Knowledge levels are closely linked to the success of exclusive breastfeeding. Research Objective: To determine the influence of lactation management health education on the knowledge level and self-efficacy of breastfeeding mothers. Research Method: Quasi-experimental with a one-group pretest-posttest design. The sample in this study consisted of 38 breastfeeding mothers at Maemunah Midwife Clinic in Bogor, from November to December 2023, using total sampling. Research Results: Before receiving health education, the majority of respondents had fair to poor knowledge (34.2%), which improved to good knowledge (73.7%) afterward. Before health education, the majority of respondents had low self-efficacy (60.5%), which increased to high self-efficacy (100%) afterward. There is an influence of lactation management health education on the knowledge level and self-efficacy of breastfeeding mothers (p-value 0.000). Conclusion and Recommendations: Lactation management health education influences the knowledge level and self-efficacy of breastfeeding mothers. It is hoped that healthcare professionals can enhance lactation education to improve the knowledge of breastfeeding mothers.